A Postzoo Future: Why Welfare Fails Animals in Zoos. (31st August 2018) - Pierce, Jessica; Bekoff, Marc
ABSTRACT: Discussions on the welfare of nonhuman animals in zoos tend to focus on incremental improvements without addressing the underlying problem of captivity. But alterations to the conditions of zoo captivity are irrelevant for animals. Real zoo reform will involve working to completely change the landscape. We offer six necessary reforms to bring zoos into a more ethical future: (1) Shut down bad zoos, now; (2) stop exhibiting animals who cannot and never will do well in captivity; (3) stop killing healthy animals; (4) stop captive breeding; (5) stop moving animals around from one zoo to another; and (6) use the science of animal cognition and emotion on behalf of animals.